2021
DOI: 10.1007/s00262-021-02863-1
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay of stromal tumor-infiltrating lymphocytes, normal colonic mucosa, cancer-associated fibroblasts, clinicopathological data and the immunoregulatory molecules of patients diagnosed with colorectal cancer

Abstract: A total of 94 patients with colorectal cancer (CRC) were included in this study. Lymphocytic infiltration of CD45+ cells in the normal colon was more pronounced than that in the paired tumor stroma (p = 0.0008). The mean immunoscore of CD45+TILs was decreased in CRC compared with the controls (p = 0.0010). The percentage of CD3+ cells was higher in stage II than in stage IV (p = 0.0218) and showed a negative correlation with the TNM classification (r = -0.2867, p = 0.0109). The number of stromal CD4+TILs was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
0
10
1
Order By: Relevance
“…This peculiar mechanism seems to emerge also from our study: the stroma-rich cases, evaluated in surgical specimens, had a lower percentage of stromal TILs (even though not statistically significant p = 0.0660), suggesting that the tumor microenvironment could determine an increased difficulty for immune cells to reach the tumor core. This particular behavior between TSR and TILs, as already proven in different tumor histotypes [ 28 , 29 ], appears to be one of the possible immune-escaping mechanisms that cancer cells establish during EMT to elude immunosurveillance. These findings are aligned with previous observations that high stroma percentage is associated with a weaker peri-tumoral inflammatory infiltrate in patients with other solid malignancies [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
“…This peculiar mechanism seems to emerge also from our study: the stroma-rich cases, evaluated in surgical specimens, had a lower percentage of stromal TILs (even though not statistically significant p = 0.0660), suggesting that the tumor microenvironment could determine an increased difficulty for immune cells to reach the tumor core. This particular behavior between TSR and TILs, as already proven in different tumor histotypes [ 28 , 29 ], appears to be one of the possible immune-escaping mechanisms that cancer cells establish during EMT to elude immunosurveillance. These findings are aligned with previous observations that high stroma percentage is associated with a weaker peri-tumoral inflammatory infiltrate in patients with other solid malignancies [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
“…The immunomodulatory effects of CAFs on CRC have been observed in a progressive rat model, in which T lymphocytes and monocytes were found outside the myofibroblast-surrounded tumors (Lieubeau et al, 1999). Recent findings have also shown that the levels of CAFs markers such as α-SMA, thrombin and fibronectin are significantly higher in CRC than in normal colonic mucosa, and α-SMA expression is negatively correlated with the number of tumor-infiltrating lymphocytes (TILs), while fibronectin displays positive coexpression (Zadka et al, 2021), and that CAF phenotypes are also correlated with CD8 + T-cell infiltration (Johnson et al, 2020), hence underscoring the importance of CAFs in regulating CRC immunity. CAFs are also positively correlated with PD-L1 expression in CRC tissues, and through secreting CXCL5, CAFs are able to promote PD-L1 expression in cancer cells (Li et al, 2019b).…”
Section: Tumor Immunitymentioning
confidence: 99%
“…In addition to chemotherapy resistance, it has been found that CAFs-derived exosomes are responsible for resistance to radiotherapy, including exosomal miR-93-5p or miR-590-3p, which prevent malignant cells from apoptosis via radiotherapy. Additionally, these CAFs-derived exosomes also participate in advanced CRC stemness [ 180 , 181 , 182 ].…”
Section: Pro-tumor Effects Of Crc-associated Fibroblastsmentioning
confidence: 99%